1989
DOI: 10.1002/j.1460-2075.1989.tb08423.x
|View full text |Cite
|
Sign up to set email alerts
|

Phytochrome activation of two nuclear genes requires cytoplasmic protein synthesis.

Abstract: We have investigated the effects of protein synthesis inhibitors on light-induced expression of two plant nuclear genes, Cab and rbcS, in wheat, pea and transgenic tobacco. Light activation of these two genes is very sensitive to cycloheximide, an inhibitor of cytoplasmic protein synthesis but not to chloramphenicol, an inhibitor of organeliar protein synthesis. Studies with chimeric gene constructs in transgenic tobacco seedlings show that cycloheximide exerts its effect at the transcriptional level. As a con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
23
0

Year Published

1990
1990
2008
2008

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 25 publications
6
23
0
Order By: Relevance
“…Previous reports (15,23), as well as this work, have shown that phytochrome activation of cab and rbcS shows relatively slow kinetics with a maximal level of mRNA accumulation reached within 6-10 h after onset of irradiation. In the present work, we found <5% of the light-inducible cab transcript 0.5 h after illumination.…”
supporting
confidence: 68%
“…Previous reports (15,23), as well as this work, have shown that phytochrome activation of cab and rbcS shows relatively slow kinetics with a maximal level of mRNA accumulation reached within 6-10 h after onset of irradiation. In the present work, we found <5% of the light-inducible cab transcript 0.5 h after illumination.…”
supporting
confidence: 68%
“…The metabolic repression of photosynthetic genes apparently overrides other forms of regulation, e.g., light, tissue type, and developmental stage (Simpson et al, 1986;Kuhlemeier et al, 1987;Schell, 1987;Ha and An, 1988;Benfey and Chua, 1989;Ueda et al, 1989) because it is executed in young leaf cells under light. In this study, the young leaf cells (greening mesophyll protoplasts) were isolated from illuminated dark-grown seedlings, which is a well-established system for the study of the photosynthetic gene expression at an early developmental stage (Nelson et al, 1984;Sheen and Bogorad, 1986a, 1986bSimpson et al, 1986;Mosinger et al, 1988;Lam et al, 1989). The greening mesophyll protoplasts of maize provide an abundant and homogeneous cell population, synchronized in photosynthetic gene induction and expression, for the study of photosynthetic gene regulation.…”
Section: Discussionmentioning
confidence: 99%
“…The efficacies of protein synthesis inhibitors may differ among plant species. Emetine and anisomycin treatment of wheat seedlings provided O and 40% inhibition, respectively (Lam et al, 1989). In contrast, both inhibitors blocked protein synthesis in pea seedlings by 85% (Theologis et al, 1985).…”
Section: Discussionmentioning
confidence: 99%